1994
DOI: 10.1063/1.358157
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Mössbauer studies of single-crystal Fe16N2 and Fe-N martensite films epitaxially grown by molecular beam epitaxy (invited)

Abstract: Single-phase, single-crystal Fe16N2(001) films and Fe-11 at. %N martensite films of 200–900 Å thickness have been epitaxially grown on In0.2Ga0.8As(001) substrates by evaporating Fe in an atmosphere of mixed gas of N2 and NH3, followed by annealing. The saturation magnetizations 4πMs’s for Fe16N2 and Fe-N martensite films have been measured to be around 29 and 24 kG at room temperature, respectively, and almost constant in the above thickness range by using a vibrating sample magnetometer. 4πMs for Fe-N marten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(72 citation statements)
references
References 24 publications
2
67
3
Order By: Relevance
“…Large magnetization value has been expected for α"-Fe 16 N 2 thin films [1][2][3] showed the saturation magnetization of 162 emu•g -1 , which was higher than 151 emu•g -1 of α-Fe powder before the nitridation, but lower than the previously reported values. The lower value was expected to be due to the effects of non-magnetic surface amorphous oxide and also Al 2 O 3 added to improve the durability of in the starting γ-Fe 2 O 3 .…”
Section: Introductioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Large magnetization value has been expected for α"-Fe 16 N 2 thin films [1][2][3] showed the saturation magnetization of 162 emu•g -1 , which was higher than 151 emu•g -1 of α-Fe powder before the nitridation, but lower than the previously reported values. The lower value was expected to be due to the effects of non-magnetic surface amorphous oxide and also Al 2 O 3 added to improve the durability of in the starting γ-Fe 2 O 3 .…”
Section: Introductioncontrasting
confidence: 43%
“…The yield of α"-Fe 16 N 2 was smaller in the ammonia nitrided product of α-Fe with the larger particle size. In our previous study, Fe 3 O 4 nanoparticle with a particle size of 40 nm prepared from aqueous solution was used as a reference of the starting powder in low temperature nitridation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then, 20 years later, that Kim and Takahashi 2 reported polycrystalline, mixed-phase Fe-N films with a saturation magnetization exceeding that of both α-Fe and Co 35 Fe 65 (∼ 2 × 10 6 A/m). However, it took another 20 years for the result to be reproduced (and, in fact, surpassed) by Sugita et al 3,4 Throughout the 1980s and '90s, other measurements of Fe 16 N 2 thin films were reported that generally did not find this large magnetic moment. [5][6][7][8] Concurrently, density-functional theory (DFT) electronic structure calculations were performed, 9-14 finding the moment per Fe ion to be modestly increased with respect to bulk bcc Fe but far short of the 3.5 µ B reported by Sugita et al It was shown 15 that LSDA+U 18 calculations could yield an average moment comparable to that of some experiments (∼ 2.8µ B per Fe), but the parameters (U ≈ 3.94, 1.0, and 1.34 eV on the 4d, 4e, and 8h sites, respectively, with J = U/10) were obtained via an embedded-cluster method with a small screening constant and were not calculated from first principles.…”
Section: Introductionmentioning
confidence: 94%
“…Mössbauer spectroscopy has been performed in many previous works 3,4,8,[38][39][40][41] , and the hyperfine field has been calculated 9,12,13,42 from DFT. Our calculated B hf (found along with our calculated Fe moments in Table I) agrees well with these past results; we find that the Fe sites with N nearest-neighbors exhibit approximately the same field (-23 and -22 T on the 4e and 8h sites), while B hf = −31 T for the 4d sites.…”
Section: A Hyperfine Fieldmentioning
confidence: 99%